Heat of the Everflame - Cole, Penn (Cole, Penn. Kindred's curse saga, 2025)
"The war has begun. Both sides demand Diem's allegiance - or her death. After her disastrous coronation, Diem finds herself at the center of the conflict between the Descended and the Guardians. With her newfound friends and the man she's falling for on one side, and the mortals she has vowed to protect on the other, Diem must walk a careful line to save the people she loves... even from each other. When the mystery of her usual heritage begins to unravel, it sends Diem and Luther on an unexpected journey across the realms. The answers they seek may hold the key to winning the war, but finding them will require Diem to face painful truths about her mother, her bloodline, and her fate. Meanwhile, the Crowns have set Diem in their sights. Some could be her greatest allies - while others want her dead. To end their oppressive reign, Diem must sort friend from foe and risk it all to build an army of her own. But a powerful figure in the north has plans that could change everything..." -- Jacket flap